Impact of mood and gender on individual investors' reactions to retractions and corrections of earnings forecasts. Issue 9 (19th February 2019) - Strydom, Maria; Scally, Amale; Watson, John
ABSTRACT: Whilst individual investors' reactions to earnings forecasts have been widely documented, the impact that retractions and/or corrections have on investors' decisions has received little attention. Further, the role that either/both mood and gender of investors play has not been investigated within this context. This is especially important as failure by individual investors to adjust correctly to retractions/corrections of earnings may have adverse investment outcomes. Our study thus investigates whether mood and gender differences influence the way in which individual investors react to retractions and corrections of management earnings forecasts. In this paper, we show that individual investors do not adjust correctly to retractions and corrections of previously disclosed information. We also find that both mood and gender play a significant role in individual investors' reactions to such announcements. Awareness of the differences in investors' reactions to retractions and corrections of earnings according to their mood and/or gender can provide further insights on whether their investment decisions are rational and are hence consistent with traditional models of assumed rational investment behaviour.